220 Functional analysis of ZFHX4 as a novel therapeutic target in ovarian cancer. (13th November 2020) - Oyama, Y; Shigeta, S; Tsuji, K; Tokunaga, H; Shimada, M; Yaegashi, N
Abstract : Introduction: Ovarian cancer is one of the most lethal gynecologic malignancies. Many patients are diagnosed in advanced stages of disease where the prognosis is poor due to the inevitable acquired resistance to platinum agents. Thus, novel therapeutic strategies effective for platinum-resistant cases are required. Zinc Finger Homeobox 4 (ZFHX4) has been known as one of the major transcription regulators in nerve and muscle differentiation. Recent researches including our genome-wide exploration indicate ZFHX4 is also involved in carcinogenesis and cancer progression. The objective of this study was to investigate the potential of ZFHX4 as a novel therapeutic target in ovarian cancer. Methods: Correlations between ZFHX4 mRNA expression and overall survival in 61 ovarian cancer cases treated at our institute and in the cases registered in TCGA database respectively were assessed by log-lank test. RNAi knockdown was introduced to several ovarian cancer cells to investigate the influence of ZFHX4 on cancer cell proliferation, migration and platinum sensitivity. [Results] Both in our clinical dataset and TCGA data, the overall survival was significantly poor in the group in which ZFHX4 is highly expressed. In cell model assay, ZFHX4 knockdown significantly suppressed ovarian cancer cell proliferation. Decreased motility was observed in the cells treated with siRNA targeting ZFHX4 by scratch assay. Furthermore, ZFHX4 knockdown increased cisplatin sensitivity. Conclusions: Altogether, our results suggest ZFHX4 functions to promote cancer cell proliferation, migration and platinum-resistance. Interruption of ZFHX4 function independently or in combination with platinum agents has a potential to bring benefit for the treatment of ovarian cancer.